Ukrainian Youth and Scholars in International Academic Mobility: Resources and Opportunities to Self-Realize - Bakhov, Ivan S.; Odarchuk, Natalia A.; Mironchuk, Tetiana A. (Journal of History Culture and Art Research, 2019)
The paper deals with the topic of international academic mobility in Ukraine. It overviews the literature by both national and international researchers on the issue under the investigation and provides a case study of the accomplishments made and pitfalls Ukrainian universities encounter on their integration into the common European educational area. Inconsistent educational legislations between contracting countries, as well as the absence of the uniform legal regulations are stated to be the basic instruments that prevent successful implementing of the programs on academic mobility and factors of major concern that exacerbate the process of students’ or teaching staff’s exchanges, when addressing the topic of academic mobility in Ukraine. A critical study of the analytical data made it possible to spot an array of administrative, managerial, financial, educational proper, and socio-cultural roadblocks that hamper Ukrainian transition into the common European educational area. The authors provide statistics on the top rates countries for Ukrainian outcoming academic mobility, and on the top-rated Ukrainian universities for incoming academic mobility. The research reveals outcoming academic mobility to overweigh incoming one in Ukraine owing to the fact the procedures of transferring a Ukrainian student to a university abroad are less complicated than those of a foreign student to Ukrainian higher education establishments. Finally, there are given suggestions on how it might be possible to align educational curricula with the European principles of higher education to foster international academic mobility in Ukraine.